2013
DOI: 10.1080/10934529.2013.797249
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of hydrogenotrophic denitrification and anammox on the improvement of the quality of the drinking water supply system

Abstract: A drinking water supply system operates at Chyasal (in the Kathmandu Valley, Nepal) for purifying the groundwater that has high levels of ammonium nitrogen (NH4-N). However, high NO3-N concentrations were seen in the water after treatment. To further improve the quality of the drinking water, two types of attached growth reactors were developed for the purification system: (i) a hydrogenotrophic denitrification (HD reactor) and (ii) a concurrent reactor with anammox and hydrogenotrophic denitrification (AnHD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results show that the activity of hydrogenotrophic denitrification was able to be enhanced at low organic content. The mechanism of hydrogenotrophic denitrification is explained in Eqn (7) 21 . Furthermore, the total N removal rate reached a maximum of ca 2.4 mg L −1 h −1 at a C/N ratio of 2.0, and later reduced to ca 1.3 mg L −1 h −1 at a C/N ratio of 1.0 in the Cu reactor and SS reactor ( ca 1.2 mg L −1 h −1 in the bioreactor). NO3+1.08CH3OH+H+0.46N2+0.76CO2+2.44H2normalO+0.065C5H7O2normalN H2+0.35NO3+0.35H++0.05CO20.17N2+1.10H2normalO+0.01C5H7O2normalN …”
Section: Resultsmentioning
confidence: 99%
“…The results show that the activity of hydrogenotrophic denitrification was able to be enhanced at low organic content. The mechanism of hydrogenotrophic denitrification is explained in Eqn (7) 21 . Furthermore, the total N removal rate reached a maximum of ca 2.4 mg L −1 h −1 at a C/N ratio of 2.0, and later reduced to ca 1.3 mg L −1 h −1 at a C/N ratio of 1.0 in the Cu reactor and SS reactor ( ca 1.2 mg L −1 h −1 in the bioreactor). NO3+1.08CH3OH+H+0.46N2+0.76CO2+2.44H2normalO+0.065C5H7O2normalN H2+0.35NO3+0.35H++0.05CO20.17N2+1.10H2normalO+0.01C5H7O2normalN …”
Section: Resultsmentioning
confidence: 99%
“…This is because H 2 concentration significantly affects the process; an increase leads to a higher bacterial growth rate, which brings about a higher efficiency [28,29]. The last results reported that 0.28 moles of H 2 could reduce 1 mol of NO 3 -N; however, a higher H 2 concentration should be applied to the system so as to reduce the limitation of H 2 [30,31]. Previous studies have suggested that DH should be maintained above 0.2 mg/L since NO 3 -N and NO 2 -N reductases can be inhibited, while NO 2 -N reductase is more sensitive than NO 3 -N reductase, causing NO 2 -N accumulation in the system [8].…”
Section: Effect Of H2 Flow Rate and Sparging Cycle Of Air And H2 Feedmentioning
confidence: 99%
“…Ammonium-nitrogen (NH 4 -N) and nitrate-nitrogen (NO 3 -N) are two main forms of nitrogen-containing species present commonly in wastewater. Previous studies by others [ 3 5 ] have shown that high NH 4 -N concentrations (40–50 and 30–40 mg/L) are seen in municipal and agricultural wastewaters, respectively. These levels are considerably greater than the acceptable levels of NH 4 -N and NO 3 -N, which are 0.5 and 5 mg/L, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 98%